Efeitos do húmus de minhoca e da inoculação do fungo micorrízico arbuscular Glomus macrocarpum Tul.&Tul. sobre o desenvolvimento de mudas porta-enxertos de cajueiro anão-precoce (Anacardium occidentale. L) - Bakker, Alexandre Pereira de (1994)
Two experiments were conducted under greenhouse conditions at the Campus of the Universidade Federal do Ceará, in Fortaleza, Ceará, Northeast of Brazil, in order to test the effects of inoculation with arbuscular mycorrhizal fungi and earthworm humus on the growth of dwarf cashew seedlings (Anacardium occidentale L.) In Experiment I, with 16 treatments and 5 replicates and 60 days long, were tested 14 different species of arbuscular mycorrhizal fungi. The substrate (S) used was a mixture of two parts of Quartz Sand and one part of Red-Yellow Latosol. The treatments were irrigated weekly with Hewitt solution without phosphorus. The Experiment II was composed of 11 treatments and 5 replicates and 50 days long. Besides substrate (S) was used another substrate composed of a mixture of two parts of Quartz Sand and one part of a Vertisol, This type of substrate is recommended by EMBRAPA/CNPAT to grow dwarf cashew seedlings. The seedlings were inoculated with the arbuscular fungus Glomus macrocarpum,Tul. & Tul. selected in Experiment I.The substrate (S) was manured with 5 different levels of organic matter (earthworm humus): 0, 50, 100, 150, 200 grams for each kilogram of substrate (S). Height of plants, axis diameter, leaf area, shoot dry matter, shoot phosphorus, and nitrogen content and percentage of root colonization were determinated. The inoculation with arbuscular mycorrhizal fungi did not provide a significative effect on the growth and nutrient content of the seedlings. The effects on the growth and nutrient contents were be caused by earthworm humus added to the substrate. The use of this kind of organic matter may be a feasible alternative for the production of dwarf cashew seedlings The substrate (SE), recommended by EMBRAPA/CNPAT, did not behave as good as the substrate (S) added with the maximum level of earthworm humus. ( 220g / Kg. of substrate). The substrate (S) added with 'the maximum level of earthworm humus (220g/Kg of substrate) was superior to the substrate (SE), recomended by EMBRAPA/CNPAT.